1963
DOI: 10.1126/science.140.3572.1236
|View full text |Cite
|
Sign up to set email alerts
|

Seed Discharge in Arceuthobium : A Photographic Study

Abstract: Photographs, made at a speed of 5 microseconds, of the ejection of the Arceuthobium seed from its fruit, show that tumbling in the vertical plane begins soon after discharge and that most seeds have turned 90 degrees when they have traveled about 6 centimeters. As the seeds leave the fruit they have a viscous sheath around the trailing end that disintegrates after the seeds have traveled about 2 to 3 centimeters. This viscous material does not act as a rudder as has been postulated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 1 publication
0
15
0
Order By: Relevance
“…Viscin tissue, a mucilaginous region that forms a layer around the single seed within each fruit, accumulates the hydrostatic force needed for water-driven explosive discharge14. Dispersal is ultimately achieved by explosive fracture in the abscission layer at the pedicel345. A somewhat analogous strategy for seed dispersal has been described for other plants, such as Ecballium elaterium (L.) A.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…Viscin tissue, a mucilaginous region that forms a layer around the single seed within each fruit, accumulates the hydrostatic force needed for water-driven explosive discharge14. Dispersal is ultimately achieved by explosive fracture in the abscission layer at the pedicel345. A somewhat analogous strategy for seed dispersal has been described for other plants, such as Ecballium elaterium (L.) A.…”
mentioning
confidence: 91%
“…1). Seminal studies by Hinds et al 3. showed that a seed can be dispersed as far as 20 m from its source, with initial velocities approaching 25 m s −1 (100 km h −1 ) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to most mistletoes, the dwarf mistletoes are primarily disseminated by an "explosive fruit" system involving both hydrostatic and mechanical mechanisms (92,94). Dwarf mistletoe seeds are expelled from fruits at initial velocities of about 24 m/s and may fly 10 m or more (Fig.…”
Section: Mistletoe Biologymentioning
confidence: 99%
“…Hinds, Hawksworth, and McGinnies (1963) found that Arceuthobium (Loranthaceae) seeds tumble in flight and that the viscin sheath, composed of gelatinous material surrounding the seeds, is separated from the seeds in a matter of microseconds after they are ejected. Hinds, Hawksworth, and McGinnies (1963) found that Arceuthobium (Loranthaceae) seeds tumble in flight and that the viscin sheath, composed of gelatinous material surrounding the seeds, is separated from the seeds in a matter of microseconds after they are ejected.…”
mentioning
confidence: 99%